2022
DOI: 10.24911/sjp.106-1616783478
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of paediatric pyogenic musculoskeletal infections in a developing country

Abstract: Background: Epidemiological data regarding paediatric pyogenic musculoskeletal infections from developing countries of Asia and Africa are sparse and is further complicated by presence of factors like malnutrition, delay in initiating treatment, belief in alternative form of treatment and under vaccination. The aim of this study is to retrospectively analyse the cases of paediatric pyogenic musculoskeletal infections in a tertiary care centre in India. Methods: It is a retrospective study including patients b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…The present study found that osteomyelitis was the most prevalent pediatric MSK infection, consistent with prior research indicating a higher incidence of osteomyelitis compared to cellulitis and septic arthritis in this population [ 5 , 13 , 14 ]. Additionally, Staphylococcus aureus was identified as the primary causative organism, accounting for 82.8% of cases.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present study found that osteomyelitis was the most prevalent pediatric MSK infection, consistent with prior research indicating a higher incidence of osteomyelitis compared to cellulitis and septic arthritis in this population [ 5 , 13 , 14 ]. Additionally, Staphylococcus aureus was identified as the primary causative organism, accounting for 82.8% of cases.…”
Section: Discussionsupporting
confidence: 92%
“…This could potentially skew the study results, especially in areas where housing prices are high but disadvantaged communities still exist [ 18 ]. Furthermore, the inclusion of pyomyositis, although not typically managed by orthopedic surgeons, was done due to its association with MSK infectious pathologies as indicated in the literature [ 5 , 13 ]. However, it is important to note that the management of these pathologies often involves a multi-specialty approach, whereas this study focused solely on orthopedic management [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of empirical antibiotic should be as per the local antibiogram and a specialty opinion regarding infectious diseases may be obtained. Clindamycin and linezolid are the antibiotics of choice in areas with methicillin-sensitive S. aureus endemicity 32) . Once the clinical and biochemical markers show improvement, oral antibiotics can be administered for replacement of the intravenous route.…”
Section: Discussionmentioning
confidence: 99%
“…Once the clinical and biochemical markers show improvement, oral antibiotics can be administered for replacement of the intravenous route. The ideal duration of antibiotic administration has not yet been determined; however, a two-week course of intravenous antibiotics followed by four weeks of oral antibiotics seems reasonable 31 32) .…”
Section: Discussionmentioning
confidence: 99%